Chimeric CYP21A1P/CYP21A2 genes identified in Czech patients with congenital adrenal hyperplasia - Vrzalová, Zuzana; Hrubá, Zuzana; Hrabincová, Eva Sťahlová; Vrábelová, Slávka; Votava, Felix; Koloušková, Stanislava; Fajkusová, Lenka (European journal of medical genetics, 2011)
Congenital adrenal hyperplasia (CAH) comprises a group of autosomal recessive disorders caused by an enzymatic deficiency which impairs the biosynthesis of cortisol and, in the majority of severe cases, also the biosynthesis of aldosterone. Approximately 95% of all CAH cases are caused by mutations in the steroid 21-hydroxylase gene (CYP21A2). The CYP21A2 gene and its inactive pseudogene (CYP21A1P) are located within the HLA class III region of the major histocompatibility complex (MHC) locus on chromosome 6p21.3. In this study, we describe chimeric CYP21A1P/CYP21A2 genes detected in our patients with 21-hydroxylase deficiency (21OHD). Chimeric CYP21A1P/CYP21A2 genes were present in 171 out of 508 mutated CYP21A2 alleles (33.8%). We detected four types of chimeric CYP21A1P/CYP21A2 genes: three of them have been described previously as CH-1, CH-3, CH-4, and one type is novel. The novel chimeric gene, termed CH-7, was detected in 21.4% of the mutant alleles. Possible causes of CYP21A1P/CYP21A2 formation are associated with 1) high recombination rate in the MHC locus, 2) high recombination rate between highly homologous genes and pseudogenes in the CYP21 gene area, and 3) the existence of chi-like sequences and repetitive minisatellite consensus sequences in CYP21A2 and CYP21A1P which play a role in promoting genetic recombination.
Keywords: Pseudogenes; Mutant Chimeric Proteins; mutantní chimérické proteiny; Humans; kongenitální adrenální hyperplazie; lidé; steroid-21-hydroxylasa; Recombination, Genetic; Czechoslovakia; rekombinace genetická; Steroid 21-Hydroxylase; DNA Mutational Analysis; pseudogeny; Adrenal Hyperplasia, Congenital; mutační analýza DNA; Československo